Antioxidative response of Indian mustard subjected to drought stress (Journal of Oilseed Brassica, 2026)
The growth and yield of plants are severely affected by different environmental stresses. Water deficit imposed by drought brings about severe growth retardation and yield loss of crops. Therefore, in order to evaluate the response of antioxidant defense system of Indian mustard varieties to drought stress, a field experiment was conducted at Oilseeds Research Area, CCS HAU, Hisar, by taking two varieties i.e. RH 0406 (drought-tolerant) and RH 0749 (drought-sensitive). A different response of drought stress was observed on enzymatic and non-enzymatic components of antioxidant system in leaves of drought-tolerant and drought-sensitive varieties of Indian mustard (Brassica juncea). Drought stress was created by withholding the irrigation after sowing. The antioxidative enzymes viz. superoxide dismutase (SOD), peroxidase (POX), ascorbate peroxidase (APX) and glutathione reductase (GR) showed higher basal activities in leaves of drought-tolerant variety (RH 0406) as compared to drought-sensitive variety (RH 0749). Plants under drought stress indicated a significant increase in antioxidative enzyme but this increase was more pronounced in droughttolerant variety i.e. RH 0406 as compared to RH 0749, a drought sensitive variety. The content of ascorbic acid, carotenoids, total glutathione and proline content were also recorded higher in tolerant variety than in sensitive variety under drought stress. It can be inferred that leaves of drought-tolerant variety (RH 0406) had greater capacity to perform reaction of antioxidative pathways under drought stress to control drought-induced oxidative stress.